Youtubers na televisão : o que pensam jovens seguidores - Rauber, Tania Mara (2018)
In the latest years, successful youtubers began to appear frequently commanding segments and even television programs. TV seeks to incorporate an alternative system, which has been successful in the network, mainly among young people, thus attracting this audience. We notice so that this process has not yet been consolidated and there was not youtubers loyalty in television programming. We propose to investigate the opinion of young followers concerned to the performance of network idols in TV programs. Do they agree? Do they prefer the youtuber on platform or on television? Considering study of specialized bibliography, questionnaire and exploratory observation, and use of qualitative-quantitative methodology, we did the fieldwork. We applied online questionnaire and gather a discussion group to debate about the presence of youtubers on TV and on YouTube. In the online questionnaire as well as in the discussion group, the participants evidences their preference for youtuber performance on the internet. Even though, they consider the presence of idols on television as something natural and that can bring benefits to professionals. However, this strategy is not seen as something of great impact, whether in the audience on TV, on Youtube itself, or in the relation between fan and idol.